1997
DOI: 10.1002/hep.510250110
|View full text |Cite
|
Sign up to set email alerts
|

The hyperventilation of cirrhosis: Progesterone and estradiol effects

Abstract: treat hypoventilation disorders. 12 Although plasma progesProgesterone and estradiol are metabolized in the terone is elevated in cirrhotic patients because of decreased liver and are elevated in patients with cirrhosis. Progeshepatic metabolism, progesterone has not been proved to terone stimulates ventilation by activating progesterone cause their hyperventilation. receptors in the central nervous system; estradiol mayWe propose estradiol as a contributing factor to respiratory facilitate progesterone's acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 29 publications
(4 reference statements)
1
10
0
1
Order By: Relevance
“…Moreover, no differences in the arterial partial pressure of oxygen was observed among the three Child-Pugh classes, nor was there any correlation with resting pulmonary ventilation. On the contrary, and consistent with the results of the previous findings [1,5,6,13], we found that patients with Child-Pugh class C cirrhosis demonstrated both alveolar hyperventilation and reduced PaCO 2 at rest compared to patients with less decompensated disease. In addition, patients in class C showed increased chemosensitivity to CO 2 and elevated values of plasma norepinephrine and serum progesterone compared to patients in class A. Progesterone is able to affect ventilation in healthy subjects and a strong correlation between PaCO 2 and serum progesterone levels has been observed in pregnant women [12].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, no differences in the arterial partial pressure of oxygen was observed among the three Child-Pugh classes, nor was there any correlation with resting pulmonary ventilation. On the contrary, and consistent with the results of the previous findings [1,5,6,13], we found that patients with Child-Pugh class C cirrhosis demonstrated both alveolar hyperventilation and reduced PaCO 2 at rest compared to patients with less decompensated disease. In addition, patients in class C showed increased chemosensitivity to CO 2 and elevated values of plasma norepinephrine and serum progesterone compared to patients in class A. Progesterone is able to affect ventilation in healthy subjects and a strong correlation between PaCO 2 and serum progesterone levels has been observed in pregnant women [12].…”
Section: Discussionsupporting
confidence: 92%
“…Several mechanisms have been proposed, including increased serum ammonia [6], hypoxia [5], and, more recently, raised sex hormones (namely progesterone) [13]. Hyperammonemia is a common finding in cirrhotic patients: however, venous ammonia concentration has not been shown to correlate with minute ventilation [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result indicates that the presence of ascites and/or the progression of disease could lead to a further increase in central respiratory drive intensity. What triggers hyperventilation is yet unknown [32] . However, hyperventilation can explain in part the close correlation between chronic dyspnea and RMS in end-stage liver disease patients without ascites.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation in the analysis of risk factors is that they were not all investigated among different studies. Immobilization, estrogen levels or inflammation, have not been specifically analyzed, although these conditions are common in hospitalized patients with cirrhosis [37,38]. Similarly intestinal bacterial overgrowth and gut translocation may lead to a pro-inflammatory state in cirrhosis.…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 97%